Commentary: Comparison of athletes' proneness to depressive symptoms in individual and team sports: Research on psychological mediators in junior elite athletes - Elbe, A.-M.; Nylandsted Jensen, S. (Frontiers in Psychology, 2016)
A commentary on: Comparison of Athletes' Proneness to Depressive Symptoms in Individual and Team Sports: Research on Psychological Mediators in Junior Elite Athletes by Nixdorf, I., Frank, R., and Beckmann, J. (2016). Front. Psychol. 7:893. doi: 10.3389/fpsyg.2016.00893